(untitled) (International journal of artificial intelligence, 2026)
When the topic of feminism or gender equality is raised, conflicts inevitably arise among people. Some say that feminism is right and should be supported, while others argue that this issue does not exist at all and that feminism leads society toward conflict. So, what exactly is feminism? And what is the difference between it and gender equality? Let’s take a closer look.